THE EFFECTIVENESS OF SIKS-NG AS AN INFORMATION SYSTEM FOR IMPROVING SOCIAL WELFARE IN KLUDAN VILLAGE - Rachma, Fanisya Lailiya; Rodiyah, Isnaini (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The purpose of this study is to describe and analyze the effectiveness of the SIKS-NG application in improving social welfare in Kludan Village. Method: The selection of informants was carried out using purposive sampling, focusing on individuals with in-depth knowledge of the implementation of SIKS-NG, including the village-level application operators. Data collection techniques consisted of observation, in-depth interviews, and documentation for primary data, as well as literature studies for secondary data, while data analysis techniques included data reduction, descriptive data presentation, and drawing conclusions with careful attention to the validity and reliability of the findings. Result: The results of the study indicate that, in terms of goal achievement, the SIKS-NG application facilitates accurate and transparent data collection and distribution of social assistance, although challenges remain regarding data validity due to feature limitations and the need for manual verification, and in terms of integration, SIKS-NG connects various relevant stakeholders such as the village government and the Social Service Office, but it still lacks direct communication features and sufficient community outreach, while in terms of adaptation, the system is responsive to regulatory changes and is supported by operator training, yet further development is needed for feedback features and technical support. Novelty: This study highlights the unique contribution of SIKS-NG in combining transparency, integration, and adaptability in the delivery of social welfare services at the village level, while also revealing the necessity of continuous feature improvement and capacity building to optimize its impact.